Genetic variations in the transcription factors GATA4 and GATA6 and bleeding complications in patients receiving warfarin therapy - Yee J; Kim W; Chang BC; Chung JE; Lee KE; Gwak HS (Dove Medical Press, 2019)
Jeong Yee,1,* Woorim Kim,2,* Byung Chul Chang,3,4 Jee Eun Chung,5 Kyung Eun Lee,2 Hye Sun Gwak11College of Pharmacy & Division of Life and Pharmaceutical Sciences, Ewha Womans University, Seoul 03760, Korea; 2College of Pharmacy, Chungbuk National University, Cheongju-si 28160, Korea; 3Department of Thoracic and Cardiovascular Surgery, Bundang CHA Medical Center, CHA University, Seongnam, Gyeonggi-do, Korea; 4Department of Thoracic & Cardiovascular Surgery, Yonsei University Medical Center, Seoul 03722, Korea; 5College of Pharmacy, Hanyang University, Ansan 15588, Korea*These authors contributed equally to this workPurpose: GATA4 and GATA6 are known to have potential roles in vascular regulation by affecting vascular smooth muscle cell differentiation and atrial natriuretic peptide levels. The aim of this retrospective study was to investigate the associations between GATA4 and GATA6 polymorphisms and bleeding complication risk at a therapeutic international normalized ratio (INR) in patients with mechanical heart valves.Patients and methods: Study patients were included from the Ewha-Severance Treatment (EAST) Group of Warfarin. It consisted of 229 patients who received warfarin therapy after undergoing mechanical heart valve replacement and maintained a stable INR (INR of 2.0–3.0 for at least three consecutive times). Twenty single-nucleotide polymorphisms including VKORC1, CYP2C9, GATA4, and GATA6 were analyzed. Multivariate logistic regression analysis was employed to investigate the independent risk factors for bleeding complications. To evaluate the potential clinical value of genotyping for preventing bleeding complications in patients with high-risk genotype, the number needed to genotype (NNG) was also calculated.Results: One hundred forty-two patients were included in this study, 21 of whom had bleeding complications. After adjusting covariates, TT genotype carriers of rs13273672 in GATA4 and CC genotype carriers of rs10454095 in GATA6 showed 5.0- (95% CI, 1.6–15.7) and 3.1-fold (95% CI, 1.1–8.7) higher bleeding complications than carriers of C allele and T allele, respectively. NNG for preventing one patient from experiencing bleeding complications in patients with TT genotype of rs13273672 and CC genotype of rs10454095 was 22.2 and 17.5, respectively. Patients with both TT genotype in rs13273672 and CC genotype in rs10454095 showed 8.7-fold (95% CI, 1.7–46.1) higher bleeding complications than those with other genotypes. NNG in patients having both TT genotype in rs13273672 and CC genotype in rs10454095 was calculated to be 40.0.Conclusions: This study showed that GATA4 and GATA6 gene polymorphisms could affect bleeding complications during warfarin treatment in patients with mechanical heart valves.Keywords: GATA4, GATA6, warfarin, bleeding, polymorphism